Hyperhidrosis. Issue 1 (January 2022) - Baker, Daryll
Abstract: Hyperhidrosis is the excess production of abnormal quantities of sweat. It affects up to 5% of the population. A careful history confirms the diagnosis and determines the sites affected and the physical and psychological severity of the problem. History and examination usually confirm the diagnosis. Most cases are 'primary' with no underlying cause, but causes of 'secondary' hyperhidrosis should be sought and treated in their own right. For most cases of hyperhidrosis, it is usual to progress along the 'hyperhidrosis treatment ladder' gradually increasing the degree of intervention. Initial treatment is with proprietary preparations such as topical antiperspirants. Botulinum toxin has also proved useful in cases of localized hyperhidrosis. Surgery, in the form of video-assisted thoracoscopic sympathectomy, is the most definitive treatment for palmar and axillary hyperhidrosis. Long-term follow-up and support is needed for most patients as long-term symptom control is required.